Tribological and thermomechanical properties of epoxy-matrix nanocomposites containing montmorillonite nanoclay intercalated with polybutadiene-based quaternary ammonium salt. (20th October 2020) - Yi, Hongling; Hu, Meiling; Yao, Donggang; Lin, Heng; Zheng, Baicun
ABSTRACT: An organic/inorganic hybrid nanocomposite material was fabricated by blending epoxy resin with hydroxyl-terminated polybutadiene-based quaternary ammonium salt (HTPB-QAS) intercalated montmorillonite (MMT). The influence of HTPB-QAS-MMT content on the tribology and thermomechanical properties of the resulting epoxy-matrix nanocomposite was studied. The results show that suitable addition of HTPB-QAS-MMT can enhance the storage modulus and wear resistance, and decrease friction coefficient of epoxy polymer. The improvement of mechanical properties of HTPB-QAS-MMT modified epoxy can be attributed to the increased interaction between MMT, intercalant HTPB-QAS and epoxy polymer. Wear surface morphology analysis shows that the friction mechanism of 2E4MI cured sample is abrasive wear. The mechanical behaviours of DDM cured samples were also studied and were compared with those of 2E4MI cured ones.